Carbon uptake of an urban green space inferred from carbonyl sulfide fluxes - Jesse Soininen; Kukka-Maaria Kohonen; Pekka Rantala; Liisa Kulmala; Hermanni Aaltonen; Leena Järvi (npj Climate and Atmospheric Science, 2025)
Abstract With several cities worldwide pursuing carbon neutrality in the upcoming decades, there is an increasing interest in quantifying cities’ anthropogenic carbon emissions using atmospheric observations. The challenge with both in-situ and remote sensing methods is, however, that the observations include both anthropogenic and biogenic signals. To reduce uncertainties in anthropogenic emission estimations, it is critical to partition biogenic fluxes of carbon dioxide (CO2) from the observed data. In this study, we, for the first time, examine the suitability of carbonyl sulfide (COS), a proxy for photosynthesis, on partitioning biogenic CO2 uptake from the ecosystem exchange measured with the eddy covariance (EC) technique over an urban area in Helsinki, Finland. The urban vegetation acts as a clear sink for COS whereas anthropogenic processes show minimal COS emissions within the source area of the measured net carbon flux. We show that two different COS flux-based methods are able to produce the dynamics of photosynthesis by an independent light-response curve-based estimation. Together with commonly used soil and vegetation respiration proxy, we removed biogenic signals from the urban net CO2 exchange and demonstrated that together with CO2 fluxes, COS flux can successfully be used to get realistic estimations of anthropogenic carbon emissions using the EC method.